Effectiveness and safety of cemented and uncemented hemiarthroplasty for the treatment of intracapsular hip fractures: a systematic review and meta-analysis of randomised controlled trials - Kumar, N; Kunutsor, S; Fernandez, M; Dominguez, E; Parsons, N; Costa, M; Whitehouse, M (British Editorial Society of Bone and Joint Surgery, 2020)
Aims We conducted a systematic review and meta-analysis to compare the mortality, morbidity, and functional outcomes of cemented versus uncemented hemiarthroplasty in the treatment of intracapsular hip fractures, analyzing contemporary and non-contemporary implants separately.